MORE WOMEN SHOULD BE MADE AWARE OF CERVICAL CANCER PREVENTION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUBANG KERIAN, KELANTAN, May 2015 Cervical cancer is one of the contributors to the mortality rate among women in the country, where 6 per cent of the 1,500 people diagnosed with this type of cancer died each year.